Pengaruh Budaya Kerja, Pelatihan dan Kompensasi Terhadap Kinerja Pegawai Dinas Pendidikan Kabupaten Labuhanbatu Utara - Andi Syahputra Nasution, Syaiful Bahri, Sjahril Effendy Pasaribu (Pusdikra Publishing, 2022)
This study aims to determine the effect of work culture, training and compensation on the performance of the Labuhanbatu District Education Office employees. The population of this study were the employees of the Education Office of North Labuhanbatu Regency, totaling 43 employees. The data collection technique in this study is a list of questions (questionnaire), while the data analysis techniques used are classical assumption test, multiple regression, t test, F test, and coefficient of determination. There is an influence of Work Culture, Training and Compensation on the Performance of Education Office Employees of North Labuhanbatu Regency which is 0.494. The value of the multiple correlation coefficient jointly between Work Culture, Training and Compensation on performance is obtained Rx1x2y = 0.703. This positive value means that if the work culture, training and compensation are improved, the performance will increase. From the F test obtained 0.793 with sig 0.005 <0.05, indicating that Ho is rejected and Ha is accepted, meaning that Work Culture (X1), Training (X2) and Compensation (X3) have a significant effect on performance (Y) at 0.05 level. The value of the coefficient of determination obtained (R-Square) is 0.494 or 49.40%, indicating about 49.40% of the Y variable can be explained by the variables of Work Culture (X1), Training (X2) and Compensation (X3) or practically it can be said that the contribution of Work Culture (X1), Training (X2) and Compensation (X3) to performance (Y) is 49.40%, the rest is influenced by other variables not examined.